Eosinophils in filarial infections: Inducers of protection or pathology? - Ehrens, Alexandra; Hoerauf, Achim; Hübner, Marc P. (Frontiers in Immunology, 2022)
Filariae are parasitic roundworms, which can cause debilitating diseases such as lymphatic filariasis and onchocerciasis. Lymphatic filariasis, also known as elephantiasis, and onchocerciasis, commonly referred to as river blindness, can lead to stigmatizing pathologies and present a socio-economic burden for affected people and their endemic countries. Filariae typically induce a type 2 immune response, which is characterized by cytokines, i.e., IL-4, IL-5 and IL-13 as well as type 2 immune cells including alternatively activated macrophages, innate lymphoid cells and Th2 cells. However, the hallmark characteristic of filarial infections is a profound eosinophilia. Eosinophils are innate immune cells and pivotal in controlling helminth infections in general and filarial infections in particular. By modulating the function of other leukocytes, eosinophils support and drive type 2 immune responses. Moreover, as primary effector cells, eosinophils can directly attack filariae through the release of granules containing toxic cationic proteins with or without extracellular DNA traps. At the same time, eosinophils can be a driving force for filarial pathology as observed during tropical pulmonary eosinophilia in lymphatic filariasis, in dermatitis in onchocerciasis patients as well as adverse events after treatment of onchocerciasis patients with diethylcarbamazine. This review summarizes the latest findings of the importance of eosinophil effector functions including the role of eosinophil-derived proteins in controlling filarial infections and their impact on filarial pathology analyzing both human and experimental animal studies.